2017
DOI: 10.1016/j.scitotenv.2016.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of commercial formulation on the sorption and leaching behaviour of propyzamide in soil

Abstract: Experiments compared sorption and leaching behaviour for the herbicide propyzamide when applied to two soils either as technical material or in the commercial formulation Kerb® Flo. Sorption was investigated in batch systems as well as using a centrifugation technique to investigate changes in pesticide concentration in soil pore water over incubation periods of up to 28days. Studies with small soil columns compared leaching of technical and formulated pesticide for irrigation events (6 pore volumes) 1, 7, 14,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…As the passage of leaching time, the release amount of Sb and As showed an increasing tendency as a whole, and the mining waste rock was seriously eroded due to the increasingly enhanced leaching scouring action, so the water and air could enter inside the mining waste rock, and react with and its internal antimony compounds and arsenic compounds, and the long-lasting oxidation to Sb and As salts in waste rocks by water would cause more Sb and As being released from the waste rock due to oxidation reduction by water and air, and then enter the leaching solution, thus making the accumulative release amount increase. Under the rainy conditions in the south, the increase of rainfall will inevitably result in the relatively easier release of Sb and As from the waste rocks into the surrounding soil and water environment, thereby causing environmental pollution [22,23].…”
Section: Effect Of Leaching Intensity On Sb and As Releasementioning
confidence: 99%
“…As the passage of leaching time, the release amount of Sb and As showed an increasing tendency as a whole, and the mining waste rock was seriously eroded due to the increasingly enhanced leaching scouring action, so the water and air could enter inside the mining waste rock, and react with and its internal antimony compounds and arsenic compounds, and the long-lasting oxidation to Sb and As salts in waste rocks by water would cause more Sb and As being released from the waste rock due to oxidation reduction by water and air, and then enter the leaching solution, thus making the accumulative release amount increase. Under the rainy conditions in the south, the increase of rainfall will inevitably result in the relatively easier release of Sb and As from the waste rocks into the surrounding soil and water environment, thereby causing environmental pollution [22,23].…”
Section: Effect Of Leaching Intensity On Sb and As Releasementioning
confidence: 99%
“…Other studies have explored the effects of formulation on pesticide behavior. In studies with chlorsulfuron, coformulants reduced sorption (Foldenyi et al ); studies with propyzamide (Khan and Brown ) showed sorption to increase; and studies with triticonazole, cyprodinil, propetamphos, and fludioxinil showed sorption to increase (Beigel et al ; Beigel and Barriuso ; Garcia‐Ortega et al ; Pose‐Juan et al ). The impacts of coformulants therefore likely depend on the a.i.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a previous study showed that the relative leaching difference between commercial pesticide formulations and technical pesticide materials increased with the solubility of pesticides in water, for example, 1.4 for azoystrobin while the factor of was 4.3 for the more water-soluble triadimenol [ 13 ]. However, no differences were observed in the adsorption of technical and formulated propyzamide, but leached mass of formulated propyzamide was significantly greater than that of technical propyzamide [ 14 ]. In other cases, several surfactants increased pesticide desorption, and hence, pesticide mobility [ 31 ].…”
Section: Introductionmentioning
confidence: 99%